PENERAPAN TEKNOLOGI FLUIDIZED BED DRYER DENGAN PENAMBAHAN ZEOLIT 3A UNTUK MENINGKATKAN EFISIENSIPENGERINGAN GABAH - Noor Hidayati; Utami Diah P.; Ratnawati Ratnawati; Suherman Suherman (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Now, drying paddy using conventional method is irrelevant to used. The need of grain increasing each year is one of the main factor that pushes scientist to invent new methods of drying paddy grain. The old method is unusefull since it takes up space, needed the sun as the drying media which causes a long drying time. One of the alternative of drying paddy grain is by using mechanic dryer. By using this type of dryer, the process of drying takes faster comparing to the old method and the distribution of grain is supplied continuously. The dryer which uses fluidized bed can be one of the solution due to its less energy consumption, a better drying result and high drying capacity. The variable used to identify drying performance is temperature and loading weight. From the experiment, it is resulted that the best temperature for drying paddy grain is 50 C with the flowrate 3,5 m/s.